2014
DOI: 10.1111/josi.12075
|View full text |Cite
|
Sign up to set email alerts
|

“Ordinary Men,” Extraordinary Circumstances: Historians, Social Psychology, and the Holocaust

Abstract: For historians the Holocaust is among the most complex historical situations inFor historians the Holocaust is among the most complex historical situations in which to try to explain perpetrator behavior. This is partly because the Holocaust differs from other forms of mass killing because of its long-term, systematic, and controlled nature, and partly because the number of men (no women were actually involved in carrying out the face-to-face killing) who played a direct part in the genocide was very great, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
(20 reference statements)
0
20
0
1
Order By: Relevance
“…For example, Haslam and colleagues () show that the experimental prod that is most clearly an order (“you have no choice, you must continue) is also least likely to produce obedience (Burger, ; Reicher, Haslam, & Miller, ). Indeed, as Haslam and colleagues argue, this raises the question of whether these obedience studies are about obedience at all (see also Overy, ).…”
Section: Milgram's Experiments: Making People Obedientmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Haslam and colleagues () show that the experimental prod that is most clearly an order (“you have no choice, you must continue) is also least likely to produce obedience (Burger, ; Reicher, Haslam, & Miller, ). Indeed, as Haslam and colleagues argue, this raises the question of whether these obedience studies are about obedience at all (see also Overy, ).…”
Section: Milgram's Experiments: Making People Obedientmentioning
confidence: 99%
“…Here, a parallel can be drawn with Asch's () line judgment studies in which those who went along with the majority reported just as much stress and confusion as those who dissented (Jetten & Hornsey, ). Yet the similarity in behavior between those who are obedient and disobedient (and those who conform vs. rebel) may not be that surprising because the same motivation may underlie both obedience and disobedience: wanting to help the experimenter and to “do the right thing” (Einwohner, ; Ent & Baumeister, ; Haslam & Reicher, ; Jetten & Hornsey, , ; Overy, ).…”
Section: Milgram's Theory: a Missed Opportunitymentioning
confidence: 99%
See 1 more Smart Citation
“…In his original article, Milgram (1963) suggested a variety of complex possible explanations for the high level of obedience he reported. A decade later, however, Milgram (1974) settled on an appealingly simplistic explanation-the "agentic state"-where the pressure from the experimenter turns the teachers into automatons focused on fulfilling their duty to him (see Overy, 2014;Reicher, Haslam, & Miller, 2014).…”
Section: Simplifying the Explanation Of Obedient Behavior: Lay Disposmentioning
confidence: 99%
“…In recent years this perspective has come under increasing scrutiny from both historians and psychologists (e.g. Haslam & Reicher, 2007;Lang, 2014;Overy, 2014). Milgram's studies were always controversial (e.g.…”
mentioning
confidence: 99%